Spatial Control of Substitutional Dopants in Hexagonal Monolayer WS2: The Effect of Edge Termination. Issue 6 (1st January 2023) - Zhang, Tianyi; Liu, Mingzu; Fujisawa, Kazunori; Lucking, Michael; Beach, Kory; Zhang, Fu; Shanmugasundaram, Maruda; Krayev, Andrey; Murray, William; Lei, Yu; Yu, Zhuohang; Sanchez, David; et al.
Abstract: The ability to control the density and spatial distribution of substitutional dopants in semiconductors is crucial for achieving desired physicochemical properties. Substitutional doping with adjustable doping levels has been previously demonstrated in 2D transition metal dichalcogenides (TMDs); however, the spatial control of dopant distribution remains an open field. In this work, edge termination is demonstrated as an important characteristic of 2D TMD monocrystals that affects the distribution of substitutional dopants. Particularly, in chemical vapor deposition (CVD)‐grown monolayer WS2, it is found that a higher density of transition metal dopants is always incorporated in sulfur‐terminated domains when compared to tungsten‐terminated domains. Two representative examples demonstrate this spatial distribution control, including hexagonal iron‐ and vanadium‐doped WS2 monolayers. Density functional theory (DFT) calculations are further performed, indicating that the edge‐dependent dopant distribution is due to a strong binding of tungsten atoms at tungsten‐zigzag edges, resulting in the formation of open sites at sulfur‐zigzag edges that enable preferential dopant incorporation. Based on these results, it is envisioned that edge termination in crystalline TMD monolayers can be utilized as a novel and effective knob for engineering the spatial distribution of substitutional dopants, leading to in‐plane hetero‐/multi‐junctions that display fascinating electronic, optoelectronic, and magnetic properties. Abstract : An edge‐dependent dopant distribution effect (i.e., sulfur‐zigzag edge terminated domains host a higher density of transition metal dopants) is demonstrated using examples of hexagonal Fe‐ and V‐doped WS2 monolayers. This work highlights the important role of edge termination in tuning the spatial distribution of dopants, which constitutes a novel knob for creating in‐plane hetero‐/multi‐junctions that locally display intriguing physicochemical properties.